APPLICATION OF ŻARĀI’ TO INTERPRETATION LEGAL VERSES TO RESOLUTE CASES OF BLASPHEMY - Widodo, Panggih; Mariani, Mariani (Ma'had Aly As'adiyah Sengkang, 2025)
This paper examines the interpretation of verses on blasphemy related to freedom of opinion and expression and explores the law of these verses using the Żarāi’ theory. Żarāi’ theory attempts to read the various intermediaries that cause something to happen and prevent intermediaries that cause something that contains evil and damage. Application of the Żarāi’ theory to QS. al-An’ām/6:108 and QS. al-Taubah/9: 64-65 produces a law that every act that can cause blasphemy must be prevented in order to avoid the evils resulting from blasphemy and things that can prevent blasphemy must be encouraged. Application of the Żarāi’ theory to this verses produces a law that freedom of opinion and expression that can trigger blasphemy must be avoided and prevented early on and things that can prevent freedom of opinion and expression from elements of blasphemy must be encouraged.